Interview expectancies: awareness of potential biases influences behaviour in interviewees. Issue 1 (2nd January 2019) - Adams-Quackenbush, Nicole M.; Horselenberg, Robert; Hubert, Josephine; Vrij, Aldert; van Koppen, Peter
Abstract : Expectancy effects are known to influence behaviour so that what is expected appears to be true. In this study, expectancy was induced using (fabricated) information about honesty and specific group membership. Targets were tested in a non-accusatory interview environment using neutral and information-gathering questions. It was hypothesized that those exposed to the negative information (the expectancy) would demonstrate behaviour consistent with an increased cognitive load, and evidence was found to support this prediction. Due to the investigative nature of the information-gathering questions, it was also expected that the targets exposed to the expectancy would exhibit more of these behaviours in the investigative portion of the interview. Some behaviour was found to support this prediction (i.e. shorter responses and increased speech disturbances); however, indicators of performance altering load were not observed during this phase of the interview. These findings support the hypothesis that expectancy effects can noticeably alter interviewee behaviour.